Dietary Fatty Acid Intakes and the Outcomes of Assisted Reproductive Technique in Infertile Women - M Jahangirifar; M Taebi; MH Nasr-Esfahani; M Heidari-Beni; GhH Asgari (JRI, 2021)
Background: The purpose of this study was evaluating the relationship between fatty acid (FA) intakes and the Assisted Reproductive Technique (ART) outcomes in infertile women. Methods: In this descriptive longitudinal study, a validated food frequency questionnaire (FFQ) was used to measure dietary intakes among 217 women with primary infertility seeking ART treatments at Isfahan Fertility and Infertility Center, Isfahan, Iran. The average number of total and metaphase II (MII) oocytes, the fertilization rate, the ratio of good and bad quality embryo and biochemical and clinical pregnancy were assessed. Analyses were performed using mean, standard deviation, Chi-square test, ANOVA, ANCOVA, logistic regression. Results: A total of 140 women were finally included in the study. There was a positive relationship between the average number of total and MII oocytes and the amount of total fatty acids (TFAs), saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFAs), linoleic acids, linolenic acids, and oleic acids intakes, while eicosapentaenoic acids (EPAs) and docosahexaenoic acids (DHAs) intakes had an inverse relationship. Consuming more amounts of TFAs, SFAs, PUFAs, MUFAs, linoleic acids, and oleic acids was associated with the lower fertilization rate, whereas the consumption of linolenic acids and EPAs increased the fertilization rate. The ratio of good quality embryo was directly affected by the amount of PUFAs intakes. Additionally, there was a negative correlation between the amount of SFAs intakes and the number of pregnant women. Conclusion: TFAs, SFA, PUFA, and MUFA intakes could have both beneficial and adverse impacts on ART outcomes.